Surgical management of a large cystic trochlear nerve schwannoma mimicking a brainstem glioma: a case report - Fimic, Miroslav; Haas, Patrick; Ortiz Rey, Jose Antonio; Tatagiba, Marcos (Frontiers in Oncology, 2024)
IntroductionIntracranial schwannomas represent a rare group of intracranial tumors, with purely motor nerve schwannomas being the rarest of them. The anatomical proximity of these tumors to the brainstem may present a radiological challenge in differentiating them from intra–axial brainstem tumors, which can influence further decision–making and treatment options.MethodsWe report on a 47–year–old male patient who was diagnosed with a large cystic intracranial tumor with radiological features suggestive of an intrinsic brainstem glioma.ResultsAfter discussing treatment options and risks based on a presumed radiological diagnosis, microsurgical treatment via lateral–suboccipital craniotomy in semi–sitting position, under continuous intraoperative neuromonitoring was performed. Intraoperative findings proved that the tumor was an extra–axial schwannoma originating from the left trochlear nerve. Gross total removal of the lesion was achieved.ConclusionDue to their rarity, non–specific symptoms and the possibility to mimicking intra–axial brainstem tumors on imaging, these tumors may present a diagnostic challenge and should be taken into account during treatment decision-making.